Australia's Little Space Travellers : the Flight Shaped Tektites of Australia - McColl, Don (Springer International Publishing : Imprint : Springer, 2017)
This book provides a showcase for the incredibly well-preserved flight-textured tektites of southern Australia, which are the world's finest known examples. It provides an overview of their forms and flight features, which can be expected to appear, at least in part, on any objects falling from space. Some of these specimens are so perfectly shaped that it is hard to believe that they have been buried in the recent strata of Australia for 770,000 years. It also discusses the history of the story of their incredible flight into space and return becoming widely accepted, which led to them being recognized as space travelers. Further, it describes their classical shapes and offers an explanation of how each developed. It provides collectors, meteoriticists, and museum curators with insights into the astounding forms of Australian tektites produced by hypersonic flight.